Emerging treatments for metastatic castration-resistant prostate cancer: Immunotherapy, PARP inhibitors, and PSMA-targeted approaches. (2020) - Marshall, Catherine Handy; Antonarakis, Emmanuel S.
Abstract: Recently there has been an explosion of new agents being investigated for the treatment of prostate cancer. These modalities represent new therapies aimed at old targets, and new therapies addressing new targets. This review will highlight three novel and emerging areas of treatment that have the potential to significantly impact the management of metastatic castration-resistant prostate cancer (mCRPC) in the near future: immunotherapy, poly ADP-ribose polymerase (PARP) inhibitors, and prostate-specific membrane antigen (PSMA)-targeted modalities. Immunotherapy, particularly immune checkpoint blockers, PARP inhibitors, and PSMA-targeted therapies are all increasingly being studied for the treatment of mCRPC although none are currently FDA-approved specifically for prostate cancer. Together these three classes of treatments may drastically change the future landscape of mCRPC. This review will cover what is currently known about the utility of these agents for the treatment of mCRPC, the areas of active research, and how these agents may be useful for patients in the future. It will also emphasize the notion of biomarker selection to help inform which patients are more likely to respond to these therapies.